The Potential Impact of Demographic Changes in Geopolitical Landscape - Pulami, Manish Jung; Nepal, Sandhya (Asian Journal of Population Sciences, 2024)
In an era marked by swift demographic changes, the population of a country emerges as a crucial source of power and progress, shaping the future geopolitical landscape. This paper explores the dynamic interplay between evolving demographic elements and their intricate relationship with geopolitics. Through a synthesis of compelling cases and data-driven analysis, the paper provides fresh perspectives on the geopolitical ramifications of demographic transitions. The research incorporates a literature review, establishing the significance of population as a determinant of national power, offering a comprehensive overview of global demographic changes, and presenting an empirical analysis that underscores the role of demographic shifts as catalysts for geopolitical consequences. The study, grounded in political demography theory, integrates demographic aspects with geopolitical implications. Employing qualitative analysis, the research utilizes both numerical and non-numerical data from secondary sources to establish connections among variables. Overall, the discussion underscores that demographic shifts, ranging from declining population growth in certain nations to youth bulges in others, will exert profound impacts on the worldwide geopolitical landscape. It emphasises the necessity for nations to proactively address demographic challenges, through strategic policies that prioritize workforce development, social welfare, and international alliances. This proactive approach is deemed essential for ensuring sustained economic and military capabilities amidst the evolving geopolitical scenario.